Bahasa Gaul, Media Sosial, dan Identitas Generasi Alpha - Nasrullah, Dafa; Anhar, Anhar; Vanya, Valerina; Ramadhani, Zalfa Octavia (Universitas Negeri Padang, 2024)
The development of digital technology and social media has brought significant changes to the way the younger generation communicates, especially the Alpha Generation. This generation, born between 2010 and 2025, often uses slang that has developed from various digital platforms such as TikTok, Instagram and YouTube. The slang used by Generation Alpha reflects social and cultural dynamics and is influenced by global digital trends. This study aims to analyze the use of slang among Generation Alpha and its impact on the development of the Indonesian language. This research uses a qualitative approach with observation and content analysis methods on various social media platforms. The research results show that slang is not only used as a means of communication, but also as a form of expression of identity and creativity. Even though this language enriches Indonesian language knowledge, there is a potential risk of reducing the quality of formal languages and the loss of regional languages. Therefore, awareness of the wise use of slang and more comprehensive language education is needed from an early age to maintain linguistic diversity in Indonesia.